Specific Features of The Development of Social and Cultural Values - Tojiboyev Azizbek Vakhobjonovich (Indonesian Journal Publisher, 2025)
This paper examines the specific features of social and cultural value development in mention a specific region, time period, or group. It analyzes how mention a key event, influence, or phenomenon, e.g., industrialization, a political shift, a cultural movement impacted the existing value system and led to the emergence of new values. The research aims to provide insights into the complex relationship between social change and cultural values